2015
DOI: 10.5603/cj.a2014.0024
|View full text |Cite
|
Sign up to set email alerts
|

Newly impaired glucose metabolism and prognosis after percutaneous revascularization

Abstract: (OR = 2.70, p = 0.029) and readmission due to heart failure during the followup (OR = 3.82, p = 0.022). Conclusions: Screening for impaired glucose metabolism after PCI permits the detection of a high proportion of patients with abnormal glucose regulations. However, previously known diabetes remains the only independent predictor of cardiovascular events in the followup. (Cardiol J 2015; 22, 1: 44-51)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Of the 1,139 studies initially identified in the search, 17 studies 3,5,[10][11][12][13][14][15][16][17][18][19][20][21][22][23] (12 prospective and five retrospective) with 11,868 (76.5% male), 14,894 (78.5% male) and 13,536 (71.1% male) patients in the prediabetes, normoglycaemia and DM groups, respectively, were included in the final analysis. Seventeen studies compared outcomes for prediabetes versus normoglycaemia, while 12 studies compared outcomes for prediabetes versus DM at the longest follow-up.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 1,139 studies initially identified in the search, 17 studies 3,5,[10][11][12][13][14][15][16][17][18][19][20][21][22][23] (12 prospective and five retrospective) with 11,868 (76.5% male), 14,894 (78.5% male) and 13,536 (71.1% male) patients in the prediabetes, normoglycaemia and DM groups, respectively, were included in the final analysis. Seventeen studies compared outcomes for prediabetes versus normoglycaemia, while 12 studies compared outcomes for prediabetes versus DM at the longest follow-up.…”
Section: Resultsmentioning
confidence: 99%
“…IGT was shown to be a predictor of long-term CV risk, while previously known and newly diagnosed diabetes were not [ 44 ]. Contrarily, a study of 374 patients who underwent PCI reported that a known history of diabetes, but not newly diagnosed diabetes or IGT, was associated with revascularization, non-fatal MI, and readmission for HF after a mean follow-up of 35.8 months [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Subgroup analysis showed male and patients younger than 75 years appeared higher one-year MACCE risk. Jimenez-Navarro et al 13 discovered that 21.4% of 374 CAD patients who underwent PCI were newly detected diabetes and previously known diabetes remained the only independent predictor of cardiovascular events in a mean follow-up of 35.8 ± 13.43 months. Tsuchida et al 14 reported 17% of the 298 patients studied had newly diagnosed DM, which was not a predictor of up to 10-year cardiovascular disease risk.…”
Section: Discussionmentioning
confidence: 99%